1997
DOI: 10.1111/j.1365-2133.1997.tb03740.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter flow cytometry as a tool to evaluate antipsoriatic therapy

Abstract: SummaryObjective comparison of different antipsoriatic therapies requires quantitative assessment of disease severity. However, clinical assessment with the widely used Psoriasis Area and Severity Index (PASI) inaccuracy. An alternative is the quantitative analysis of different epidermal cell parameters using multiparameter flow cytometry. Our aim in the present study was to compare the clinical and flow cytometric approach to monitor disease activity and to evaluate antipsoriatic efficacy. Clinical scores f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In order to quantify the severity of psoriatic plaques at the cellular level, a flow cytometric triple parameter method has been developed by Van Hooijdonk et al (43), and Glade et al (17) using markers for keratin 10 (RKSE60), mesenchymal cells (vimentin), and DNA content (TO‐PRO‐3 iodide). These three parameters are assessed in epidermal cell suspensions and have proven to correlate highly significant with the clinical parameters for scaling, erythema, and plaque thickening, respectively, as represented by the Psoriasis Area and Severity Index (PASI (14)) (17). They have proven to be very useful in quantifying the efficacy of antipsoriatic drugs (18, 19, 30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantify the severity of psoriatic plaques at the cellular level, a flow cytometric triple parameter method has been developed by Van Hooijdonk et al (43), and Glade et al (17) using markers for keratin 10 (RKSE60), mesenchymal cells (vimentin), and DNA content (TO‐PRO‐3 iodide). These three parameters are assessed in epidermal cell suspensions and have proven to correlate highly significant with the clinical parameters for scaling, erythema, and plaque thickening, respectively, as represented by the Psoriasis Area and Severity Index (PASI (14)) (17). They have proven to be very useful in quantifying the efficacy of antipsoriatic drugs (18, 19, 30).…”
mentioning
confidence: 99%
“…The aim of the present study was to establish a new flow cytometric protocol with simultaneous staining for keratin 1/10, keratin 6/16, and DNA content, in order to be able to assess the dynamics of all keratin 1/10 and keratin 6/16 subpopulations, and to assess the proliferative activity of these subpopulations. In particular, we tried to adapt the protocol of Van Hooijdonk et al (43) and Glade et al (17) by replacing the inflammation marker vimentin by a hyperproliferation marker.…”
mentioning
confidence: 99%
“…Epidermal thinning was observed as a result of clobetasol while calcipotriol led to increased thickness of the epidermis. Glade et al 10 . used flow cytometric methods to differentiate between the anti‐inflammatory, growth‐inhibiting and keratinization‐enhancing properties of several antipsoriatic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Calcipotriol is a synthetic vitamin D 3 analogue for the topical treatment of chronic plaque-stage psoriasis. Calcipotriol induces differentiation and inhibits proliferation of keratinocytes both in vitro and in vivo coupled with immunomodulatory activity [3, 4, 5]. Several large-scale clinical studies have demonstrated the safety and efficacy of treatment with calcipotriol either in ointment or cream formulation [6, 7, 8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%